ANALYSIS OF THE INFLUENCE OF OGANIZATIONAL TRUST, WORK ENVIRONMENT, AND SOCIAL CAPITAL ON THE PERFORMANCE OF EXCLUSIVE BREASTFEEDING PROGRAM AT THE SURABAYA CITY HEALTH CENTER - Agustyoko, Sugeng; Rochmah, Thinni Nurul; Adianti, Talia Puspita (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2024)
The Surabaya City Health Center's exclusive breastfeeding program has not met its 72.5% target from 2018-2021. A study analyzing the impact of organizational trust, work environment, and social capital on the program's performance revealed that most factors were unfavorable. The study found that trust, work environment, and social capital significantly impacted the process performance of the breast milk work team. The study concluded that these factors significantly impacted the achievement of the exclusive breastfeeding program. To improve the program's success, the Health Office suggested training breast milk counselors for the team and evaluating the consolidation mechanism. The Community Health Center also distributed tasks evenly, awarded the team, and proposed a budget for funding program activities. The findings highlight the need for improved support for exclusive breastfeeding programs in Surabaya.